Desktop 3D printing of controlled release pharmaceutical bilayer tablets - Khaled, Shaban A.; Burley, Jonathan C.; Alexander, Morgan R.; Roberts, Clive J. (Elsevier, 2014)
Three dimensional (3D) printing was used as a novel medicine formulation technique for production of viable tablets capable of satisfying regulatory tests and matching the release of standard commercial tablets. Hydroxypropyl methylcellulose (HPMC 2208) (Methocel™ K100M Premium) and poly(acrylic acid) (PAA) (Carbopol® 974P NF) were used as a hydrophilic matrix for a sustained release (SR) layer. Hypromellose® (HPMC 2910) was used as a binder while microcrystalline cellulose (MCC) (Pharmacel® 102) and sodium starch glycolate (SSG) (Primojel®) were used as disintegrants for an immediate release (IR) layer. Commercial guaifenesin bi-layer tablets (GBT) were used as a model drug (Mucinex®) for this study. There was a favourable comparison of release of the active guaifenesin from the printed hydrophilic matrix compared with the commercially available GBT. The printed formulations were also evaluated for physical and mechanical properties such as weight variation, friability, hardness and thickness as a comparison to the commercial tablet and were within acceptable range as defined by the international standards stated in the United States Pharmacopoeia (USP). All formulations (standard tablets and 3D printed tablets) showed Korsmeyer-Peppas n values between 0.27 and 0.44 which indicates Fickian diffusion drug release through a hydrated HPMC gel layer.